Model of Social and Environmental Accountability Based on the Tri Hita Karana Concept in Village Credit Institutions in Bali (E-Jurnal Akuntansi, 2026)
This research aims to determine the social and environmental accountability at Village Credit Institutions (LPDs) in Bali, based on the Tri Hita Karana (THK) cultural concept. Employing an interpretive paradigm, data was collected through documentation techniques, in-depth interviews, and direct observation. Qualitative analysis techniques, utilizing ethnographic methods, were employed to reduce, present, and conclude data, as well as to interpret its meaning. Social and environmental accountability, incorporating the THK cultural concept across the aspects of parahyangan, pawongan, and palemahan, has been implemented through the harmonization of relationships among these three aspects. The findings suggest that such harmonization can be effectively implemented both internally and externally within the institutions. Therefore, the 'Harmony' model of social and environmental accountability has been realized in LPDs in Bali.
Keywords: Akuntabilitas sosial lingkungan; Tri Hita Karana; LPD